Comparative Evaluation of Analgesic, Anti-inflammatory and Antipyretic Effects of Synthetic Derivatives of Organoantimony (?) Ferocenyl Benzoate with Piroxicam (Bangladesh Pharmaceutical Journal, 2016)
The current study was planned to evaluate comparative anti-inflammatory, analgesic and anti-pyretic activities of two newly synthesized organo-antimony (v) ferrocenyl benzoate derivatives with piroxicam. Anti-microbial activity of these compounds was also screened against two microorganisms. Analgesic effect of test compounds was evaluated by formalin-induced paw licking test in mice. The test compounds at 50 and 100 mg/kg b.w. doses exhibited significant (p